Modelação das trocas energéticas em videira com base em termometria de infra-vermelhos - Rodrigues, P. (2011)
Com o objectivo de validar um modelo de estimação da transpiração da videira a partir da medição da temperatura radiativa da superfície da sebe, instalou-se um ensaio numa vinha da casta Touriga Nacional, na região do Dão. Além de permitir caracterizar a evolução diurna dos componentes do balanço energético, conclui-se que o modelo permite uma boa estimação dos valores diários da transpiração---------------------------------------------ABSTRACT--In order to validate a model to estimate vine evapotranspiration based on its surface temperature, measured with infrared thermometers, a field trial was established in a vineyard in the Dão region. Vines were fully irrigated with a drip irrigation system. Soil water content was measured with capacitive sensors down to a 2 m depth. Surface temperature was measured with infrared thermometers (Tr), positioned above the plants so as to assure that only fully exposed leaves were viewed by the instrument. Climatic variables were measured at the same time in a nearby meteorological station. The model developed separates net radiation measured over the surface (Rn) between the components of the canopy, vines (Rnc) and soil+soil cover (Rns). To calculate sensible heat flux from the vines (Hc) using Tr, instead of the aerodynamic temperature, an additional resistance between the leaves and the mean source of the flux is introduced. Latent heat flux from the plants (lEc) is then calculated as the residual term of the energy balance. Results show that the model properly estimates transpiration from the vines, and thus that it is possible to study energy fluxes in partial cover/row crops with a simplified, low maintenance and reliable set of equipment